2013
DOI: 10.1080/17461391.2013.866166
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of shot success for basketball free throws: Visual search strategy

Abstract: In ball games, players have to pay close attention to visual information in order to predict the movements of both the opponents and the ball. Previous studies have indicated that players primarily utilise cues concerning the ball and opponents' body motion. The information acquired must be effective for observing players to select the subsequent action. The present study evaluated the effects of changes in the video replay speed on the spatial visual search strategy and ability to predict free throw success. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
0
24
0
2
Order By: Relevance
“…The accuracy of the collegiate players and recreational players for missed shots was lower than that of the non-athletes. In addition, the differences between the accuracy in each group and random chance (50%) were compared according to a study conducted by Uchida and Mizuguchi [3]. The accuracy of the collegiate players and recreational players for missed shots was lower than random chance in the first three phases (collegiate players: t<-3.65, p<0.001 in all instances; recreational players: t<-2.26, p<0.05 in all instances), but no such difference was observed in the non-athlete group in any shot phase (t>-1.13, p>0.12 in all instances).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the collegiate players and recreational players for missed shots was lower than that of the non-athletes. In addition, the differences between the accuracy in each group and random chance (50%) were compared according to a study conducted by Uchida and Mizuguchi [3]. The accuracy of the collegiate players and recreational players for missed shots was lower than random chance in the first three phases (collegiate players: t<-3.65, p<0.001 in all instances; recreational players: t<-2.26, p<0.05 in all instances), but no such difference was observed in the non-athlete group in any shot phase (t>-1.13, p>0.12 in all instances).…”
Section: Discussionmentioning
confidence: 99%
“…Aglioti and Cesari [2] asked basketball athletes, spectators (coaches or journalists) and novices to predict the success of free throws and found that the athletes responded earlier and more accurately than the other two groups of participants. Similarly, Uchida and Mizuguchi [3] compared the anticipation performance of experienced basketball players and novices observing a basketball PLOS ONE | https://doi.org/10.1371/journal.pone.0227521 January 6, 2020 1 / 10 a1111111111 a1111111111 a1111111111 a1111111111 a1111111111…”
Section: Introductionmentioning
confidence: 99%
“…Значущими у плані наукової дискусії є обґрунтовані протиріччя, що виникають: з однієї сторони -безапеляційним є необхідність якісного планування процесу підготовки команд [3,8]; з другої -неможливим є врахування впливу змінних процесів глобалізації спорту вищих досягнень у повному обсязі [2,10,15,18]. На думку авторів, що займаються вивченням питань якісної підготовки спортсменів та особливостями формування планів підготовки, важливою є інформація щодо кількісно-якісних показників гравців та їх реальної можливості взяти участь у підготовчому процесі команди [7,12].…”
Section: результати та обговоренняunclassified
“…To date, no study has investigated the effects of the use of slow-motion footage on anticipatory judgments in racket sports. Moreover, two studies did not support the effectiveness of the use of slow-motion footage on anticipatory judgments in other types of rapid movements ( Lorains et al, 2013 ; Uchida et al, 2014 ). Uchida et al (2014) showed that in the anticipation task of free throw shot success in basketball, the anticipation accuracy of experienced players decreased when they viewed the slow-speed motion condition (half speed).…”
Section: Introductionmentioning
confidence: 97%